2016
DOI: 10.1093/ips/olw011
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Relations Rather Than Clashes of Civilizations: When and How Is Religion Compatible with Democracy?

Abstract: This study develops and examines the concept of hegemonic religion and its relationship with democracy. A religion is hegemonic not only when the state grants that religion exclusive material and political privileges and benefits, but also when the religion is a core element of national identity and citizenship. We empirically examine the link between hegemonic religion and democracy using the Religion and State round 2 (RAS2), Polity, and CIRI datasets. We specifically use religious education policy, financin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The content of particular religious ideas is more or less favorable for liberal democracy and good governance. A strong debate has developed regarding the relative (dis)advantages of Christianity versus Islam in this regard (see, e.g., Cesari and Fox, ). The relative strength of religious ideas is also important.…”
Section: Review Of Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…The content of particular religious ideas is more or less favorable for liberal democracy and good governance. A strong debate has developed regarding the relative (dis)advantages of Christianity versus Islam in this regard (see, e.g., Cesari and Fox, ). The relative strength of religious ideas is also important.…”
Section: Review Of Empirical Evidencementioning
confidence: 99%
“…However, the above relationship must be put into perspective (see, e.g., Cesari and Fox, ). First, the relationship is not deterministic, as some democratic Muslim countries exist and some predominantly Christian countries in Latin America or Africa are not democratic.…”
Section: Review Of Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Others focus on transition where religion features prominently including the democratic transitions during the Arab Spring (Ferrero 2018), suggesting that democracy is harder to achieve when a hegemonic religion is tied to the state (Cesari and Fox 2016). In this vein, Mecham (2017) examines Islamist political mobilization across peaceful and violent settings.…”
Section: An Endogenous View Of Religious Mobilizationmentioning
confidence: 99%
“…Studies have also shown that hegemonic Islam has an influence on the democratic level of Muslim countries. In other words, the presence of hegemonic traits, such as religiously based laws, the financing of religion, and religious education policy, is strongly connected to a lack of democracy (Cesari and Fox 2016).…”
mentioning
confidence: 99%